Comparative analysis of main performance indices shown by world best basketball players at most important competitions - Stonkus, S. (Education. Physical training. Sport, 1998)
Objective and abounding in information performance indices shown by world best basketballers at the most important official contests is an important landmark of the aim pursued. The article aims at establishing and evaluating the performance of the best basketball players avoiding the use of standard methods: thus, one of the main criteria used was the quantitative performance indices shown per unit of time, i. e. per one minute of the game. The article contains the analysis of performance indices, such as scoring, the number of different throws made and their efficiency, etc. shown by players performing different functions, e. g. those of playmakers, side forwards and centre forwards, at the 1994 world championship and the Olympic Games held in 1996. The best basketballers of the world demonstrate excellent level of preparedness at Olympic Games. Most of the main performance indices show a tendency towards improvement what has been confirmed by a comparative analysis of the play models set for the year 1986 and the adequate performance indices shown at the Olympic Games of the year 1996. Some indices of the year 1996, e. g. the efficiency of free throws made by centre forwards and side forwards, the accuracy of distant throws made by playmakers, do not exeed the level of the play models set for the year 1986. The latter circumstance can be accounted for by the changes that have taken place in the structure of attacks, the conditions of the game and the improved defence.